Heterogeneity of professional goals among residents enrolled in a palliative care track: results of a national online survey in France - François Chaumier; Denis Angoulvant; Emmanuel Gyan; Laurent Calvel (Medical Education Online)
Background Palliative care (PC) is recognized as a universal right, aimed at improving the quality of life for patients and their families facing life-threatening conditions. Training healthcare professionals, particularly physicians, is crucial for high-quality PC. Currently, France lacks a Palliative Medicine residency or fellowship (PMR-F), offering only a Palliative Care tracks (PCT) for voluntary postgraduate students. The aim of this study was to describe motivations and career plans of students enrolled in the PCT and to identify the proportion of those who would have preferred a PMR-F if it had been available.Methods A national online survey was conducted between April and August 2024 among 128 students enrolled in PCT. A 12-item questionnaire, using a 10-point Likert scale, was designed and pilot-tested by PC educators and former students. The questionnaire was sent to identify their motivations and career plans.Results The response rate was 76% (97/128). For 76% (74/97) of students, the purpose was to acquire skills complementary to their original specialty. While 48% (47/97) also aimed to gain skills for future specialist PC practice, only 10% (10/97) enrolled due to the lack of a specialized certificate. Career plans varied, with 30% intending to practice in their original discipline and 31% in PC facilities. Finally, 23% of students aiming to work in specialized PC facilities planned to continue their training with a continuing medical education program in PM (7/30).Discussion The findings align with the official objectives of a track, emphasizing complementary skills acquisition. Our study reveals the coexistence of a variety of professional goals and projects within the same class of residents, which does not seem relevant for the same training program. It highlights the opportunity for setting up, in addition to PCT, a specialized PM curriculum in France, to better address specialized training needs for future PM experts.